Efficiency versus Maqashid Sharia Index: an Application on Indonesian Islamic Bank - Aam S. Rusydiana; Irman Firmansyah (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
The Development of Islamic Banking Industry in Indonesia relatively shows a good tendency. In the market, inefficiency would be the great obstacles in head to head to conventional bank. Despite of efficiency performance in Islamic Bank, Islamic Bank also must have sharia compliance performance. So it needed to identified the efficiency of Islamic Bank in Indonesia and the achievement of Maslahah in term of three aspects, there are education, the creating of justice, and the attainment of welfare. This study would try to measure the efficiency of Islamic Banking Industry with Data Envelopment Analysis (DEA) method and also to evaluate the performance by using Maqasid Sharia Index (MSI). Banxia Frontier Analyst 3.1 used in the data calculation. The calculation of the level of Islamic Bank efficiency in this study are relative, not absolute. Result of this study indicate four main findings, first, Islamic bank involve in quadran 1 is Islamic bank who reached the highest efficiency and the best performance; there are BMI and Bank Panin Sharia. Islamic bank involve in quadran 2 is Islamic bank who reached the highest efficiency and the lowest performance, there are BSM, Maybank Sharia, and Bank Sharia Bukopin. Islamic bank involve in quadran 3 is Islamic bank who reached the lowest efficiency and have a good performance, there are BRI sharia, and BCA sharia. Islamic bank involve in quadran 4 is Islamic bank who reached the lowest efficiency and the lowest performance, there are Bank Mega Sharia, Victoria Sharia, BNI Sharia, and BJB Sharia.Keywords: Maqasid Index, Efficiency, DEA, Efficiency-Maqasid Quadrant (EMQ)Â